Ramadan effect on stock market return and trade volume: Evidence from Dhaka Stock Exchange (DSE) - Md. Hashibul Hassan; Md. Shahidullah Kayser (Cogent Economics & Finance, 2019)
A predictable pattern of stock market return is the violation of the efficient market hypothesis (EMH). It is well studied and evident in financial literature that stock markets around the world have predictable patterns, e.g. calendar effect, behavioural effect, and Religious festival effect. By analysing market return and trading volume data of Dhaka Stock Exchange (DSE) over the period of 1 January 2002 to 30 August 2018, this study attempts to investigate the association of Ramadan, the holy month for the Muslims, with the market return, volatility and trade volume in the of DSE. Applying GJR-GARCH (p,q) model on the market return of DSE, this study concludes that Ramadan month has no significant relationship with stock market return and volatility. However, Ramadan has a significant negative impact on the daily trade volume of DSE. This is might be the outcome of decreased trading and banking hour and religious perception of investors.
Keywords: G11; G12; G14; G40; 330; Calendar anomaly; GARCH; Moving calendar event; Ramadan effect; Dhaka Stock Exchange (DSE)